Right-shoring: Making resilient offshoring and reshoring decisions. Issue 3 (June 2019) - Hilletofth, Per; Eriksson, David; Tate, Wendy; Kinkel, Steffen
Abstract: The purpose of this special topic forum is to look at some current literature on the right-shoring debate. The papers that were selected for the special topic form use a range of qualitative and quantitative methodologies to answer specific research questions related to the right-shoring phenomenon. Each of the papers is summarized in this editorial to show the findings, implications and future research directions. The ideas from these manuscripts were used as a foundation to discuss the way in which research in this area should progress. What types of questions should we be asking as we seek to discover the best "shore"? What factors and variables should we consider in our future decisions? Are there differences across regions of the world? Research in this area has continued to progress, largely because of significant global economic, environmental and regulatory changes. The "shoring" decision appears to be an area where research is keeping up with, or potentially leading practice, but there is still more opportunity to advance decision making. The included papers address a number of factors related to specific geographies and factors related to the movement of manufacturing and products and services from one location to another.